Upcycling for repurposing waste into creative products - Boonpracha, Jong; Chanplin, Panupong; Ngampipat, Chutima; Sermsri, Nichanant (Creativity Studies, 2024)
Upcycling is the process of repurposing non-used materials or products to make them more valuable or usable, with increased quality and value. However, truly little research has been conducted on the design process and/or creative ideation of upcycling in order to produce higher-quality and more valuable products. This study presents the four stages of the design process, consisting of selecting the waste products, emerging conceptions, generating ideas, and rendering a series of creative ideas. SCAMPER (substitute, combine, adjust, modify, put to other uses, eliminate, reverse), one of the practical and effective techniques to create various creative ideas, was applied in the stages of emerging conceptions and generating ideas. With the upcycling concept of waste product design utilizing SCAMPER, the results demonstrated that waste soft drink cans could be converted into five creative products: a desk watch, a picture frame, a spring paper clip, a pencil holder, and a lamp. The five products featured the upcycling of waste soft drink cans, removing the need to recycle or send them to landfills at that point in their lifecycle. Consideration was given to the design process’ compatibility with creative concept generation and design. The study indicated that upcycling should be viewed as an essential component of waste management and repurposing in order to provide an intelligent answer to escalating product waste problems.